High specificity THz metamaterial-based biosensor for label-free transcription factor detection in melanoma diagnostics - Richter, Merle; Loth, Yannik; Wigger, Anna Katharina; Nordhoff, Daniela; Rachinger, Nicole; Weisenstein, Christian; Boßerhoff, Anja Katrin; Bolívar, Peter Haring (Scientific Reports, 2023)
In this work, we present a promising diagnostic tool for melanoma diagnosis. With the proposed terahertz biosensor, it was possible to selectively and sensitively detect the early growth response protein 2, a transcription factor with an increased activity in melanoma cells, from a complex sample of cellular proteins. Fundamentally, the sensor belongs to the frequency selective surface type metamaterials and consists of a two-dimensional array of asymmetrically, doubly split ring resonator unit cells. The single elements are slits in a metallic layer and are complemented by an undercut etch. This allows a selective functionalization of the active area of the sensor and increases the sensitivity towards the target analyte. Hereby, specific detection of a defined transcription factor is feasible.
CRIS-Team Scopus Importer:2023-12-08